2021
DOI: 10.3390/metabo11060335
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Metabolic Imaging of Energy Metabolism in Traumatic Brain Injury Using Hyperpolarized [1-13C]Pyruvate and Dichloroacetate

Abstract: Hyperpolarized magnetic resonance spectroscopic imaging (MRSI) of [1-13C]pyruvate metabolism has previously been used to assess the effects of traumatic brain injury (TBI) in rats. Here, we show that MRSI can be used in conjunction with dichloroacetate to measure the phosphorylation state of pyruvate dehydrogenase (PDH) following mild-to-moderate TBI, and that measurements can be repeated in a longitudinal study to monitor the course of injury progression and recovery. We found that the level of 13C-bicarbonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that DCA is a pharmacological agent that activates PDH by inhibiting PDK and also shows significant neuroprotective potential. The administration of DCA has been suggested to facilitate local lactic acid removal [ 32 ], tumor therapy [ 33 ], and pulmonary hypertension [ 34 ]. However, the protective effect, molecular mechanism, and blood-brain barrier permeability of DCA in cerebral IS and I/R injury have been rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that DCA is a pharmacological agent that activates PDH by inhibiting PDK and also shows significant neuroprotective potential. The administration of DCA has been suggested to facilitate local lactic acid removal [ 32 ], tumor therapy [ 33 ], and pulmonary hypertension [ 34 ]. However, the protective effect, molecular mechanism, and blood-brain barrier permeability of DCA in cerebral IS and I/R injury have been rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…122 Furthermore, dichloroacetate coadministration, a PDH kinase inhibitor, showed no difference in PDH activity, indicating aerobic metabolism reduction is not due to PDH kinase inhibition. 53 Interestingly, all studies using 1-13 C-pyruvate to date have employed MRSI as the detection method, highlighting its potential as an early, noninvasive imaging modality for identifying cerebral metabolic changes in otherwise radiographically normal TBI patients. 55 Further, the use of such technology in tandem with machine learning workflows was recently shown to be capable of predicting long-term behavior changes after TBI in animals that otherwise lack detectable changes in conventional imaging at the same timepoint, 137 which suggests isotope tracing may be a powerful approach to better study the link between TBI and the elevated risk of developing long-term neurobehavioral sequelae including mental health disorders 138 and dementia, 139 among others.…”
Section: C-pyruvate Tracingmentioning
confidence: 99%
“…Pyruvate, the product of glycolysis, can be converted into lactate or acetyl CoA. TBI has been found to inhibit both the expression and activity of pyruvate dehydrogenase (PDH) 51–53 in rats, potentially shifting pyruvate metabolism toward lactate. Clinical studies suggest impaired mitochondrial pyruvate metabolism in TBI, leading to decreased aerobic respiration at the location of injury 54,55 .…”
Section: Bioenergetic Disturbance In Tbimentioning
confidence: 99%
“…43 DeVience et al assessed the extent of traumatic brain injury in rats by magnetic resonance spectroscopy (MRS) of hyperpolarized [1-13C] pyruvate and found that DCA (200 mg/kg) increased the bicarbonate/lactate ratio on both sides of the brain and attenuated the inhibition of PDH, but they did not assess whether DCA protects neurons. 44 DCA (50 and 100 mg/kg/day) was observed to shorten the latency to seizures in a second-hit flurothyl test in the mouse Figure 2 The role of DCA in cerebral ischaemia-reperfusion injury. Notes: When there is ischaemia-reperfusion injury, ATP deficiency causes the cell membrane ion pump to malfunction and intracellular calcium levels to rise.…”
Section: Hypoglycaemic Brain Injury Traumatic Brain Injury and Epilepsymentioning
confidence: 99%